Comparison of different exercise modalities on fatigue and muscular fitness in patients with multiple sclerosis: a systematic review with network, and dose–response meta-analyses - Zhang, Xi-Nuan; Liang, Zhi-De; Li, Ming-Da (Frontiers in Neurology, 2024)
BackgroundFatigue and muscular fitness are closely related to the quality of life in patients with multiple sclerosis (MS). However, the optimal exercise dosage to improve these outcomes remains unclear.ObjectiveWe evaluated the effects of different exercise modalities and dosages on fatigue levels and muscular fitness in patients with MS.MethodsA systematic search was conducted across five electronic databases, including randomized controlled trials involving exercise interventions for patients with MS. The data covered literature from the establishment of each database up to August 2024. Two independent reviewers assessed the quality of the studies. Network and dose–response meta-analyses were performed using a random-effects model to evaluate the impact of exercise.ResultsA total of 84 papers were included, involving 3,786 participants. The network meta-analysis revealed that mind–body exercise (MBE) had the most significant effect on reducing fatigue (SMD = −0.94; 95% CrI: −1.3 to −0.6), followed by resistance training (RT) (SMD = −0.86; 95% CrI: −1.2 to −0.58), combined exercise (COM) (SMD = −0.70; 95% CrI: −1.2 to −0.22), and high-intensity interval training (HIIT) (SMD = −0.50; 95% CrI: −1.1 to 0.14). Additionally, HIIT were found to be the most effective in improving muscular fitness (SMD = −0.86; 95% CrI: −1.5 to −0.27), followed by COM (SMD = −0.81; 95% CrI: −1.2 to −0.41), MBE (SMD = −0.64; 95% CrI: −1.1 to −0.16), and RT (SMD = −0.62; 95% CrI: −0.89 to −0.16). Moreover, a dose as low as 240 METs-min/week was sufficient to improve fatigue, while a dose of 430 METs-min/week was required to enhance muscular fitness. The optimal dose for reducing fatigue was 650 METs-min/week, and the best dose for improving muscular fitness was 530 METs-min/week.ConclusionExercise is an effective method for improving fatigue and muscular fitness in patients with MS. While MBE and COM rank relatively higher compared to other exercise modalities. The optimal exercise dosage for reducing fatigue and improving muscular fitness ranges between approximately 530 to 860 MET-minutes per week.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, CRD42024577643.